cyclo-Tetrakis(μ-naphthalene-1,8-dicarboxylato)tetrakis[diaqua(2,2′-bipyridine)manganese(II)] tetrahydrate - Chen, Ling (International Union of Crystallography, 2010)
In the title centrosymmetric tetranuclear complex, [Mn(4)(C(12)H(6)O(4))(4)(C(10)H(8)N(2))(4)(H(2)O)(8)]·4H(2)O, two independent Mn(II) ions are coordinated in a slightly disorted octahedral environment by two aqua ligands, two naphthalene-1,8-dicarboxylate (1,8-nap) ligands and one bis-chelating 2,2′-bipyridine (2,2′-bipy) ligand. In the crystal, molecules are linked by intermolecular O—H⋯O hydrogen bonds into chains along [100]. These chains are further linked by weak π–π interactions with centroid–centroid distances in the range of 3.609 (2)–3.758 (1) Å, forming a three-dimensional supramolecular network.